1998
DOI: 10.1097/00005131-199805000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes of "Floating Elbow" Injuries in Adult Patients

Abstract: Based on the present data, we could not clarify the factors influencing the final functional outcome after floating elbow injury. These injuries, however, potentially have many complications, such as infection or nonunion, especially when there is associated brachial plexus injury. We consider that floating elbow injuries are severe injuries and that surgical stabilization is needed; beyond that, there are no specific forms of surgical treatment to reliably guarantee excellent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 19 publications
1
50
0
4
Order By: Relevance
“…[1][2][3]5,6 Rogers et al 3 reported 100% nonunion rate of humeral fractures treated nonsurgically. Yokoyama et al 6 recommended stable internal fixation after reviewing 14 cases. Simpson and Jupiter 4 stated in their review article that when the floating elbow affects the joint, open reduction, and internal fixation is advisable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]5,6 Rogers et al 3 reported 100% nonunion rate of humeral fractures treated nonsurgically. Yokoyama et al 6 recommended stable internal fixation after reviewing 14 cases. Simpson and Jupiter 4 stated in their review article that when the floating elbow affects the joint, open reduction, and internal fixation is advisable.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Moreover, floating dislocated elbow is an extremely rare lesion. 7,8 Three cases have been reported in the english literature.…”
mentioning
confidence: 99%
“…En las dos últimas décadas se publicaron algunos casos clínicos aislados 12-15 y dos series de pacientes 16,17 que analizaron de forma detallada la influencia de diversos factores en los resultados funcionales. Yokoyama y cols.…”
Section: Figuraunclassified
“…Yokoyama y cols. 16 (1998) presentaron una serie de 15 codos flotantes evaluados (14 pacientes), con resultados funcionales sin diferencias estadísticas entre los tratados en la urgencia o los diferidos, aquellos con fracturas abiertas o cerradas, o con lesión neurovascular o sin ella, a pesar de lo cual hacen referencia al riesgo de las lesiones asociadas del plexo braquial y los nervios periféricos.…”
Section: Figuraunclassified
See 1 more Smart Citation